2002
DOI: 10.1029/2000pa000594
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of marine and terrestrial climate variability during marine isotope stages 6 and 5: Results from Santa Barbara Basin ODP Hole 893A

Abstract: [1] Planktonic foraminiferal d 18 O, pollen, and opal records from Santa Barbara Basin are used to evaluate climate changes in the northeast Pacific during marine isotope stages (MIS) 6 and 5. While the oak and foraminifera record the major glacial-interglacial changes, opal is not correlated with these large-scale transitions. Surface water warming in the basin was synchronous with terrestrial warming but earlier than ice sheet melting and increasing Northern Hemisphere insolation at Termination II. During an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Since there are no clear seasonal signals in test flux, there is little potential for a seasonal bias in δ 18 O values to result from changes in test flux. Furthermore, Friddell et al [2002] found little difference (<0.05 permil) between averaged flux‐weighted δ 18 O values and averaged δ 18 O values for these species in comparing months and years with distinctive patterns of test flux.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Since there are no clear seasonal signals in test flux, there is little potential for a seasonal bias in δ 18 O values to result from changes in test flux. Furthermore, Friddell et al [2002] found little difference (<0.05 permil) between averaged flux‐weighted δ 18 O values and averaged δ 18 O values for these species in comparing months and years with distinctive patterns of test flux.…”
Section: Discussionmentioning
confidence: 78%
“…Individuals of G. bulloides collected over the San Pedro Basin in early spring had the compact morphology and lived around 100 m, well beneath the thermocline, whereas samples from upwelling conditions indicate a mixed layer signature [ Sautter and Thunell , 1991a; Spero and Lea , 1996]. Over the SBB, δ 18 O values reflect the species‐specific predicted calcite values for G. bulloides at 20 m, or below that depth, better than those at the surface [ Pak and Kennett , 2002], but do track seasonal and interannual fluctuations of SST [ Thunell et al , 1999; Friddell et al , 2002]. Comparison of δ 18 O values from G. bulloides and N. pachyderma in a deep trap (470 m) with those from a trap at 65 m below the surface indicates that both species acquire a portion of their δ 18 O signature from below 65 m [ Pak and Kennett , 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last interglacial (MIS 5e), pollen deposited in Santa Barbara Basin (SBB) (ODP Hole 893A) from drought-adapted, Mediterranean type vegetation was comparable to, or even more expansive, than present (Heusser, 1995;Friddell, 2002). A short, mid-Wisconsinan pollen record in an organic deposit at Diamond Lake (~30 km east from Lake Elsinore) records expansion of more mesic montane ecosystems to lower elevations during near-peak glacial conditions (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…During the last interglacial (MIS 5e), pollen deposited in the Santa Barbara Basin (SBB; ODP Hole 893A) from drought-adapted, Mediterranean type vegetation was comparable to or even more expansive than present (Heusser, 1995;Friddell et al, 2002). Low resolution pollen-based reconstructions (ODP Hole 893B) suggest that drought-adapted vegetation also expanded during the Medieval Climate Anomaly (MCA) and shifted gradually toward more mesic Quercus/Pinus woodlands and forests during the Little Ice Age (LIA) at~AD 1300e1400 (Heusser, unpublished).…”
Section: California Vegetation and Climatementioning
confidence: 98%